Systematic review and meta‐analysis of cannabinoids in palliative medicine. Issue 2 (5th February 2018) - Mücke, Martin; Weier, Megan; Carter, Christopher; Copeland, Jan; Degenhardt, Louisa; Cuhls, Henning; Radbruch, Lukas; Häuser, Winfried; Conrad, Rupert
Abstract: We provide a systematic review and meta‐analysis on the efficacy, tolerability, and safety of cannabinoids in palliative medicine. The Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, PsycINFO, PubMed, Scopus, andhttp://clinicaltrials.gov, and a selection of cancer journals were searched up until 15th of March 2017. Of the 108 screened studies, nine studies with a total of 1561 participants were included. Overall, the nine studies were at moderate risk of bias. The quality of evidence comparing cannabinoids with placebo was rated according to Grading of Recommendations Assessment, Development, and Evaluation as low or very low because of indirectness, imprecision, and potential reporting bias. In cancer patients, there were no significant differences between cannabinoids and placebo for improving caloric intake (standardized mean differences [SMD]: 0.2 95% confidence interval [CI]: [−0.66, 1.06] P  = 0.65), appetite (SMD: 0.81 95% CI: [−1.14, 2.75]; P  = 0.42), nausea/vomiting (SMD: 0.21 [−0.10, 0.52] P  = 0.19), >30% decrease in pain (risk differences [RD]: 0.07 95% CI: [−0.01, 0.16]; P  = 0.07), or sleep problems (SMD: −0.09 95% CI: [−0.62, 0.43] P  = 0.72). In human immunodeficiency virus (HIV) patients, cannabinoids were superior to placebo for weight gain (SMD: 0.57 [0.22; 0.92]; P  = 0.001) and appetite (SMD: 0.57 [0.11; 1.03]; P  = 0.02) but not for nausea/vomiting (SMD: 0.20 [−0.15, 0.54]; P  = 0.26). Regarding side effects in cancer patients, there were no differences between cannabinoids and placebo in symptoms of dizziness (RD: 0.03 [−0.02; 0.08]; P  = 0.23) or poor mental health (RD: −0.01 [−0.04; 0.03]; P  = 0.69), whereas in HIV patients, there was a significant increase in mental health symptoms (RD: 0.05 [0.00; 0.11]; P  = 0.05). Tolerability (measured by the number of withdrawals because of adverse events) did not differ significantly in cancer (RD: 1.15 [0.80; 1.66]; P  = 0.46) and HIV patients (RD: 1.87 [0.60; 5.84]; P  = 0.28). Safety did not differ in cancer (RD: 1.12 [0.86; 1.46]; P  = 0.39) or HIV patients (4.51 [0.54; 37.45]; P  = 0.32) although there was large uncertainty about the latter reflected in the width of the CI. In one moderate quality study of 469 cancer patients with cancer‐associated anorexia, megestrol was superior to cannabinoids in improving appetite, producing >10% weight gain and tolerability. In another study comparing megestrol to dronabinol in HIV patients, megestrol treatment led to higher weight gain without any differences in tolerability and safety. We found no convincing, unbiased, high quality evidence suggesting that cannabinoids are of value for anorexia or cachexia in cancer or HIV patients.